Preferential Th1 Cytokine Profile of Phosphoantigen-Stimulated Human Vγ9Vδ2 T Cells - Margaret R. Dunne; Bozgana A. Mangan; Laura Madrigal-Estebas; Derek G. Doherty (Mediators of Inflammation)
Human Vγ9Vδ2 T cells recognise pyrophosphate-based antigens (phosphoantigens) and have multiple functions in innate and adaptive immunity, including a unique ability to activate other cells of the immune system. We used flow cytometry and ELISA to define the early cytokine profiles of Vγ9Vδ2 T cells stimulated in vitro with isopentenyl pyrophosphate (IPP) and (E)-4-hydroxy-3-methyl-but-2 enyl pyrophosphate (HMB-PP) in the absence and presence of IL-2 and IL-15. We show that fresh Vγ9Vδ2 T cells produce interferon-γ (IFN-γ) and tumour necrosis factor-α (TNF-α) within 4 hours of stimulation with phosphoantigen, but neither IL-10, IL-13, nor IL-17 was detectable up to 72 hours under these conditions. Cytokine production was not influenced by expression or lack, thereof, of CD4 or CD8. Addition of IL-2 or IL-15 caused expansion of IFN-γ-producing Vγ9Vδ2 T cells, but did not enhance IFN-γ secretion after 24–72 hours. Thus, phosphoantigen-stimulated Vγ9Vδ2 T cells have potential as Th1-biasing adjuvants for immunotherapy.